Business Performance and Farmers' Motivation in the Application of Hybrid Corn Variety Innovation in Lengkiti District - Yusniar, Yusniar; Efrianti, Rini; Oktarina, Yetty (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
This study aims to determine the performance of farmers and the level of motivation of farmers in using hybrid corn seed assistance and the factors that influence farmers in pursuing corn farming in Lengkiti District, Ogan Komering Ulu Regency. This research is located in Bandar Jaya, Fajar Jaya, and Tanjung Agung Villages, Lengkiti District, Ogan Komering Ulu Regency. Respondent farmers were corn farmers in Bandar Jaya, Fajar Jaya, and Tanjung Agung villages who were selected using the Simple Random Sampling Method of as many as 97 people. The time of conducting the research is around November 2021. The analysis used to answer the first objective is qualitative and quantitative analysis. Qualitative analysis is used to explain each indicator variable. Quantitative analysis will be used on the variables of productivity and farm income. The analysis used to answer the factors that influence farmers in using government-assisted hybrid seeds with the factors studied are Education (X1), Age (X2), Family Dependents (X3), and Government Policy (X4). The average income of farmers who work on corn farming in the research area, both farmers who use hybrid seeds from the government or not, is IDR. 13,680,484.53. Farmer's age variable has a significant effect partially on the motivation of farmers who use hybrid seeds provided by the government in the study area, while the rest does not affect farmers' motivation.